An Update on Evaluation in the Latin American and Caribbean Region - Chianca, Thomaz (Journal of MultiDisciplinary Evaluation, 2005)
This short paper updates the evaluation scene in the Latin American and Caribbean (LAC) region. Specifically, it covers four aspects of that scene: (1) evidence on the growing number of job opportunities for evaluators in the region, (2) news about national-level evaluation organizations, (3) professional development courses available in 2005, and (4) the internal evaluation system supported by the Brazilian federal government.